Nanocrystalline cellulose isolated from oil palm empty fruit bunch and its potential in cadmium metal removal - Lim, Yong Hui; Chew, Irene Mei Leng; Choong, Thomas Shean Yaw; Tan, Mei Ching; Tan, Khang Wei (EDP Sciences, 2016)
NanoCrystalline Cellulose (NCC) was isolated via ultrasonic cavitation assisted acid hydrolysis method. Characterization was done using Dynamic Light Scattering (DLS) together with Scanning Electron Microscope (SEM) imaging to double prove the existence of NCC. DLS measures length of 236.6 nm with width of 34.40 nm, supported by SEM which showed NCC a rod-like shaped particle with large surface area and high porosity. It was then attempted for heavy metal cadmium ion (Cd2+) removal from aqueous solution. The pH implication to the rate of Cd2+ adsorption was investigated by varying the solution to pH 4, pH 7 and pH 10 over a duration of 120 minutes. The removal efficiency was analyzed using Atomic Absorption Spectroscopy (AAS) resulting in pH 7 being the most favorable for Cd2+ removal.